Osteoarthritis of the sternoclavicular joint: is clavicular length a risk factor? - Vadgaonkar, Aditya; Darwich, Ali; Gravius, Sascha; Hackl, Michael; Rink, Johann; Janssen, Sonja; Baumgärtner, Tobias; Obertacke, Udo (Archives of orthopaedic and trauma surgery, 2025)
Osteoarthritis (OA) is the most prevalent disorder of the Sternoclavicular Joint (SCJ), with a reported lifetime prevalence of approximately 50%, yet it is rarely observed in individuals under the age of 35. When symptomatic, it manifests with pain and swelling. Although OA is strongly age-related, the influence of biomechanical factors - such as clavicular length - remains unknown.
Gesehen am 11.09.2025